ACE gene polymorphism and long-term renal graft function - Viklický, O; Hubácek, J A; Pitha, J; Teplan, V; Heemann, U W; Lácha, J; Vítko, S (Clinical biochemistry, 2001)
OBJECTIVES: The long-term outcome of transplanted kidneys has not changed substantially and only a minority of grafts survives more than 15 yr. The aim of this study was to determine the influence of ACE gene polymorphism on long-term outcome after renal transplantation. DESIGN AND METHODS: Using PCR, we evaluated ACE I/D gene polymorphism in a group of patients with long-term graft function (LTF) over 15 yr and compared it with control groups of transplant recipients and population sample. RESULTS: The distribution of genotypes in the LTF group differed from transplant controls (p < 0.05). Moreover, DD homozygotes in the LTF group had better creatinine clearance (DD: 1.1 +/- 0.3, ID: 0.96 +/- 0.3, II: 0.76 +/- 0.3 mL/s; p < 0.05). There were no differences in genotype distribution between transplant and population samples. CONCLUSIONS: Results of our study have demonstrated a possible connection between the DD variant of ACE I/D gene polymorphism and excellent long-term graft function.
Keywords: Peptidyl-Dipeptidase A; angiotensin konvertující enzym; Humans; lidé středního věku; polymorfismus genetický; kreatinin; Female; Aged; dospělí; výsledek terapie; senioři; lidé; Genotype; Creatinine; Polymorphism, Genetic; časové faktory; Adult; transplantace ledvin; ženské pohlaví; Male; Middle Aged; Treatment Outcome; polymerázová řetězová reakce; Polymerase Chain Reaction; Kidney Transplantation; genotyp; mužské pohlaví; Time Factors